The Effect of China on ASEAN: The BRI Projects in Myanmar - Ali Demir (Frequency of International Relations (FETRIAN), 2022)
This article focuses on China's gaining favourable approaches in ASEAN as a result of its investment in BRI projects within ASEAN countries. The study tries to explain both how China-Myanmar bilateral relations have developed and how Myanmar's position in ASEAN can be a possible "ally" of China by addressing China's BRI projects in Myanmar. The article focused on some of China's unfinished BRI projects, especially in Myanmar, and touched upon China's geostrategic goals through Myanmar. ASEAN's economic dependence on China and the need to maintain China's economic and political dominance in the Southeast Asian region make BRI projects both an economic lifeline and an endless interdependence for both parties. The US-China tension in the region and China's growing military capacity lead ASEAN countries to follow the "hedging strategy". However, due to countries such as Myanmar and Cambodia that have close economic and political relations with China, it remains unclear what position ASEAN will take in the future.